Surgical Excision of Dumbbell-shaped Vagus Nerve Schwannoma: A Case Report - O., Amy; T., Kalai; B., Anusha; Y, Zakinah (IIUM Medical Journal Malaysia, 2020)
Schwannoma is a benign peripheral nerve sheath tumour that arises from the uncontrolled proliferation of Schwann cells. Intracranial and extracranial vagus nerve schwannoma is an extremely rare entity that poses a surgical challenge due to its delicate location in the cerebrum and parapharyngeal space adjacent to major neck vessels. This report describes a unique case of a 42 years old female with left dumbbell vagus nerve schwannoma, involving both the intracranial and extracranial portion of the left vagus nerve, extending into the parapharyngeal space. She underwent a two-stage surgery in which intracranial vagus schwanomma was debulked initially, and excision of the extracranial schwanomma in the parapharyngeal space was performed in a later setting via a transcervical approach.